Open Sinus Lift Surgery and the Importance of Preoperative Cone-Beam Computed Tomography Scan: A Review - Rahpeyma, Amin (J Int Oral Health, 2015)
Open sinus lift surgery is a form of pre-prosthetic surgery for increasing the quality and quantity of bone in the posterior region of the maxilla. Pre-operative assessment of the maxillary sinus is essential for the success of this surgery. PubMed search was carried out in English language literature for open sinus lift surgery and cone-beam computed tomography (CBCT). The results focused on anatomic variants, vascular anatomy, complications, osteotomy/ostectomy window dimensions and thickness of the Schneiderian Membrane. 59 articles were included in this review. Features other than the height and the width of the residual alveolar ridge that should be evaluated in preoperative CBCT scan include the thickness of the lateral maxillary sinus wall, the presence of the alveolar antral artery and its diameter, the maxillary sinus floor width and angulation, irregularity of sinus floor, intimate relation of Schneiderian membrane with the roots of the adjacent teeth, sinus septum, and the quality of subantral bone. Other conditions that occasionally may be observed in special situations are also explained. More than ten parameters should be checked in evaluating CBCT images of paranasal sinuses other than the width and the length of the residual ridge in the posterior region of the maxilla. Each of them may have a significant impact on the results of the open sinus lift surgery.